2022
DOI: 10.1002/cti2.1359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adaptive natural killer cells, KLRC2 genotype and cytomegalovirus reactivation on late mortality in patients with severe COVID‐19 lung disease

Abstract: Objective SARS‐CoV‐2 infection results in severe lung disease in up to 50% of hospitalised patients. The aetiopathogenesis in a subset of such patients, who continue to have progressive pulmonary disease following virus clearance, remains unexplored. Methods We investigated the role of NKG2C+/NKG2A− adaptive natural killer (ANK) cells, KLRC2 genotype and cytomegalovirus (CMV) reactivation in 22 such patients. Results The median duration of virus positivity was 23 days, and the median duration of hospitalisatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, in CMV-exposed patients, these NKG2C + ANK cells have been found to proliferate in response to a variety of viral pathogens, including HIV, Hepatitis C Virus (HCV), Hantavirus, influenza, and pox viruses ( 16 , 28 31 ). The unique nature of this non-antigen-specific recall response against a wide variety of pathogens puts NKG2C + ANK cells at the forefront in the battle against novel pathogens such as SARS-CoV-2 ( 3 , 32 36 ), where the antigen-specific adaptive response generated from T and B cells are absent at the outset of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in CMV-exposed patients, these NKG2C + ANK cells have been found to proliferate in response to a variety of viral pathogens, including HIV, Hepatitis C Virus (HCV), Hantavirus, influenza, and pox viruses ( 16 , 28 31 ). The unique nature of this non-antigen-specific recall response against a wide variety of pathogens puts NKG2C + ANK cells at the forefront in the battle against novel pathogens such as SARS-CoV-2 ( 3 , 32 36 ), where the antigen-specific adaptive response generated from T and B cells are absent at the outset of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SARS-CoV-2 infection, in vitro studies have demonstrated that the viral spike protein-1 (SP-1) upregulates NKG2A on NK cells and HLA-E on the infected lung epithelial cells, causing a strong inhibition of cytotoxicity of NK cells ( 43 ). Our group has demonstrated a correlation between the high expression of NKG2A, the suppression of NKG2C, and the adverse outcome following severe COVID-19 lung disease, despite viral clearance ( 36 ). It is possible that the adverse effect of KLRC2 deletion genotype as reported earlier ( 32 ), was mitigated by Mw.…”
Section: Discussionmentioning
confidence: 99%
“…However, in CMV exposed patients, these NKG2C + ANK cells have been found to proliferate in response to a variety of viral pathogens, including HIV, HCV, Hantavirus, influenza, and pox viruses[16; 26; 27; 28; 29]. The unique nature of this non-antigen specific recall response against a wide variety of pathogens, puts NKG2C + ANK cells at the forefront in the battle against novel pathogens such as SARS-CoV-2 [3; 30; 31; 32; 33; 34], where antigen-specific adaptive response generated from T and B cells are absent at the outset of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SARS-CoV-2 infection, in-vitro studies have demonstrated that the viral spike protein-1 (SP-1) upregulates NKG2A on NK cells and HLA-E on the infected lung epithelial cells, causing a strong inhibition of cytotoxicity of NK cells[40]. Our group has demonstrated a correlation between high expression of NKG2A, suppression of NKG2C, and adverse outcome following severe COVID-19 lung disease, despite viral clearance[34]. It is possible that the adverse effect of KLRC2 deletion genotype as reported earlier[30], was mitigated by Mw.…”
Section: Discussionmentioning
confidence: 99%
“…48 Among these, the interaction of NKG2C/CD94 with HLA-E ligand stimulate the NK cell responses against virus-infected cells. [49][50][51] The reliable evidence indicated that there are a direct relationship between the absence of NKG2C receptor with virus infections severity. 52 The similar result was reported by Jordier et al in 2020.…”
Section: Nk Cell Dysfunction Is Linked With Increased Viral Susceptib...mentioning
confidence: 98%